Partial spike gene sequencing for the identification of SARS-CoV-2 variants circulating in Cameroon in 2021 - Monamele, Chavely Gwladys; Sadeuh-Mba, Serge Alain; Ilouga, Pauliana Vanessa; Moumbeket, Moïse Henri Y; Messanga, Loique Landry E; Mounchili Njifon, Aristide; Madaha, Estelle L; Njankouo, Ripa M; Tagnouokam-Ngoupo, Paul Alain; Tchatchueng, Jules Brice M; Tejiokem, Mathurin Cyrille; Perraut, Ronald; et al. (The Journal of Infection in Developing Countries, 2024)
Introduction: Global monitoring of severe acute respiratory syndrome related coronavirus 2 (SARS-CoV-2) genetic sequences and associated metadata is essential for coronavirus disease 2019 (COVID-19) response. Therefore, Sanger's partial genome sequencing technique was used to monitor the circulating variants of SARS-CoV-2 in Cameroon. Methodology: Nasopharyngeal specimen was collected from persons suspected of SARS-CoV-2 following the national guidelines between January and December 2021. All specimens with cycle threshold (Ct) below 30 after amplification were eligible for sequencing of the partial spike (S) gene of SARS-CoV-2 using the Sanger sequencing method. Results: During the year 2021, 1481 real time reverse transcriptase polymerase chain reaction (RT-PCR) SARS-CoV-2 positive samples were selected for partial sequencing of the S gene of SARS-CoV-2. Amongst these, 878 yielded good sequencing products. A total of 231 probable variants (26.3%) were identified. The variants were mainly represented by Delta (70.6%), Alpha (15.6%), Omicron (7.4%), Beta (3.5%), Mu (1.7%) and Gamma (0.4%). Phylogenetic analysis of the probable variants from Cameroon with reference strains confirmed that all prior and current variants of concern (VOC) clustered with their respective reference sequences. Conclusions: The surveillance strategy implemented in Cameroon, based on partial sequencing of the S gene enabled identification of the major circulating variants and provided information on the distribution of these variants, which contributed to implementing public health measures to control disease spread in the country.